Controlled delivery of essential oils for the management of rhinoceros beetle (Oryctes rhinoceros L.) in coconut - Ravindran, P.; Subaharan, Kesavan; V. Vibina, K.P. Chandran; K.P. Sonu, T.M. Subrahmaniyan (Journal of Plantation Crops, 2019)
Rhinoceros beetle, Oryctes rhinoceros L. (Coleoptera: Scarabaeidae), causes damage to coconut palms by feeding on the unopened fronds affecting photosynthesis. Management measures adopted include use of chemical insecticides and bioagents. Though chemical insecticides are effective, the undesirable effect on human and non-target organisms have led to dependence on botanochemicals for pest management. Essential oils derived from plant parts have the ability to cause desired control on insect pest. The limitation for use at field level is attributed to quick decline in its efficacy due to evaporation and photo degradation. Hence, this study aims to develop a polymer based delivery matrix for the release of essential oils more effectively. Essential oils (citriodora, basil and ajowan) and major constituent thymol, caused growth regulating effect in O. rhinoceros at 0.1 per cent. Among the essential oils screened, matrix loaded with basil and citriodora oils were superior with only 18 and 22 per cent incidence of spindle damage, respectively. Pest infestation in the control plots were over 74 per cent. The physical properties of the polymer matrix and dissipation pattern of actives loaded into the sheet were determined. This offers a potential to be incorporated as a component in IPM measures of rhinoceros beetle.